The Influence of Financial Distress, Auditor Firm Size, and Auditor Switching on Audit Delay - Tiara Putrirury Alamanda; Nugraha (www.amertainstitute.com, 2025)
This study aims to analyze the factors influencing audit delay in the consumer cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the period 2019–2022. Audit delay, which refers to the time lag between the end of the fiscal year and the issuance date of audited financial statements, is a critical aspect affecting the timeliness and relevance of financial reporting. The independent variables examined in this study include financial distress, the size of the public accounting firm (PAF), and auditor switching—factors that have been widely discussed in previous literature as potential determinants of audit timeliness. To address the research objectives, this study adopts a quantitative research approach, utilizing both descriptive and causal analysis techniques to explain the relationship between the selected independent variables and audit delay. The research sample was selected using purposive sampling, resulting in 24 companies that met the established criteria, producing a total of 96 firm-year observations over the four-year period. The empirical findings reveal that financial distress does not have a statistically significant effect on audit delay, indicating that the financial condition of the firm may not influence the timeliness of audit completion in this sector. Similarly, the size of the public accounting firm also shows no significant impact on audit delay, suggesting that larger or more reputable firms do not necessarily complete audits more efficiently. In contrast, auditor switching is found to have a positive and statistically significant effect on audit delay, implying that changes in the auditor are likely to extend the audit completion time, potentially due to the additional effort required by incoming auditors to understand the client's business and accounting systems. These findings contribute to the understanding of audit timeliness in the consumer cyclicals sector and may provide insights for regulators, investors, and company management regarding the factors that influence audit delay.